PERCERAIAN DI ERA DIGITAL : MENGANALISIS FAKTOR DAN DAMPAK TREN CHEATING DALAM PERSPEKTIF DEMOGRAFI SOSIAL - Kenny Syalwatyarsa; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
This research aims to find out what are the factors that influence the occurrence of divorce due to infidelity in this digital era, how the impact of the problem is and what efforts can be given to minimize the occurrence of divorce due to infidelity. The method used in this research is quantitative with a descriptive approach. Quantitative method is a type of research by taking random samples and then collecting data using statistical data analysis. Descriptive research is research that uses the illustrative method, the aim is to provide a detailed explanation of the problems that exist in society. Individual primary data is the data used in this study and obtained from research respondents. The results of this study indicate that divorce due to infidelity through social media occurs in the younger generation who are more fluent in using technology. Efforts to minimize the occurrence of such divorces are by reducing the use of social media, building good communication with each other, making time for spouses, and improving the quality of religious values.